Different Growth Promoting Effects of Endophytic Bacteria on Invasive and Native Clonal Plants - Dai, Zhi-Cong; Fu, Wei; Wan, Ling-Yun; Cai, Hong-Hong; Wang, Ning; Qi, Shan-Shan; Du, Dao-Lin (Frontiers in Plant Science, 2016)
The role of the interactions between endophytes and alien plants has been unclear yet in plant invasion. We used a completely germ-free culture system to quantify the plant growth-promoting (PGP) effects of endophytic bacteria Bacillus sp. on aseptic seedlings of W. trilobata and of its native clonal congener W. chinensis. The endophytic bacteria did not affect the growth of W. chinensis, but they significantly promoted the growth of W. trilobata. With the PGP effects of endophytic bacteria, relative change ratios of the clonal traits and the ramets' growth traits of W. trilobata were significantly greater than those of W. chinensis. Our results indicate that the growth-promoting effects of endophytes may differ between invasive and native clonal plants, and the endophytes of invasive plant may be host-specific to facilitate plant invasion.